2019
DOI: 10.3390/rs11050501
|View full text |Cite
|
Sign up to set email alerts
|

Flood Inundation Mapping of the Sparsely Gauged Large-Scale Brahmaputra Basin Using Remote Sensing Products

Abstract: Sustainable water management is one of the important priorities set out in the Sustainable Development Goals (SDGs) of the United Nations, which calls for efficient use of natural resources. Efficient water management nowadays depends a lot upon simulation models. However, the availability of limited hydro-meteorological data together with limited data sharing practices prohibits simulation modelling and consequently efficient flood risk management of sparsely gauged basins. Advances in remote sensing has sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…The simulated flood inundation maps of both hurricanes were transferred from HEC-RAS to a GIS 230 environment as raster files to process and compare with the observed data. Flood mapping performance is evaluated by using categorical verification statistics, which are usually implemented for estimating the accuracy of flood forecasts (Bhatt et al, 2017;Bhattacharya et al, 2019). The categorical verification statistics measure the correspondence between estimated and observed inundation patterns.…”
Section: Performance Metricsmentioning
confidence: 99%
“…The simulated flood inundation maps of both hurricanes were transferred from HEC-RAS to a GIS 230 environment as raster files to process and compare with the observed data. Flood mapping performance is evaluated by using categorical verification statistics, which are usually implemented for estimating the accuracy of flood forecasts (Bhatt et al, 2017;Bhattacharya et al, 2019). The categorical verification statistics measure the correspondence between estimated and observed inundation patterns.…”
Section: Performance Metricsmentioning
confidence: 99%
“…Furthermore, in a case study in Sri Lanka, Alahacoon et al [16] combined the trend analysis from gridded observed rainfall data with flood maps derived from satellite SAR and multispectral data to analyze the spatiotemporal patterns of floods. Using satellite TRMM rainfall data, Bhattacharya et al [17] looked at flood modelling of the sparsely gauged but very large-scale Brahmaputra basin using the HEC-HMS hydrological model. Complementing TRMM rainfall with data from the Gravity Recovery and Climate Experiment (GRACE) satellite mission, Sun et al [18] used an index for flood potential to generate monthly terrestrial water storage anomalies in order to better understand the parameters affecting the hydrological state of the Yangtze River basin.…”
Section: Overview Of Contributionsmentioning
confidence: 99%
“…Many studies and articles on the use of RS and/or GIS methods in flood mapping have been published in the literature [15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Knowing the geographical extent of submerged regions during flood occurrences is crucial for organizing relief studies as well as detecting faults with flood control facilities [29].…”
Section: Introductionmentioning
confidence: 99%